Quality Factors of Management for Vocational Education Institutions - Amnaj Panhirun; Boonchan Sisan; Pariyaporn Tungkunanan; Rachan Boontima (My University, 2019)
Abstract Given the rapid advancements faced in modern times, effective leadership is pivotal to the achievement of desired goals, competitiveness and overall success in organizations. This study aims to investigate the construct validity of management quality for vocational education institutions. The sample was 350 directors and deputy directors from vocational education institutions in Thailand, determined through Multistage Random Sampling and the research tool was a questionnaire with content validity and covering 7 sets of factors with a reliability of 0.98. The correlation of variables as determined by Kaiser- Meyer-Olkin is 0.983 and Bartlett’s test of sphericity is statistically significant. Therefore, the correlation of variables are sufficient for factor analysis. The results from the construct validity investigation of the quality management measurement model of vocational education institutions by the second order confirmatory factor analysis show that the model conforms to the empirical data derived from Chi-Square= 915.32, df= 857 and p= 0.08167 while χ 2 is not significantly different from 0 at the level of 0.05 and χ 2 /df is lower than 2 at 1.0680. In addition, RMSEA= 0.014 and RMR= 0.012, both lower than 0.05, and GFI= 0.900 and CFI= 1.00, higher than 0.90. It was concluded that the quality management measurement model of vocational education institutions has construct validity and conforms to the empirical data.
Keywords: Validity; Sample (material); Content Validity; Quality and Supply Management